Digital product passports - a tool to facilitate textile reuse and recycling practices? A study of the digital product passport’s usability in second-hand retail, textile sorting and recycling - Mosslind,Maja (2025)
The textile industry generates large amounts of waste, most of which is incinerated or landfilled. To enhance circular practices, the Ecodesign for Sustainable Products Regulation will introduce digital product passports (DPPs) in the EU. The passports will collect data on textiles throughout their value chain and are expected to become mandatory by 2027. The existing research on the DPP usability for textile reuse and recycling is limited. Therefore, this study examined how DPPs could facilitate textile reuse and recycling and what barriers exist to their implementation and effective use. Data was gathered using a qualitative exploratory research methodology, employing both a literature review and semi-structured interviews with 12 experts and practitioners managing used textiles. The results indicate that the DPPs, by providing information on, for example, material and chemical content, have the potential to facilitate textile recycling. Furthermore, they can verify authenticity and provide detailed product information, which may enable more second-hand sales. However, their current potential to facilitate sorting for reuse at sorting facilities appears limited, as they cannot determine a textile’s condition. Additional possibilities include optimizing textile flows by collecting data and raising stakeholder awareness to influence more sustainable consumption. Identified barriers include concerns about whether the data carrier containing the DPP, for example an RFID chip, will be compatible with recycling processes and how to build infrastructure to manage used textiles both with and without DPPs. Concerns were also raised regarding data inaccuracy, costs and the time required to scan the DPPs. Facilitating more textile reuse and recycling could reduce incineration and landfilling, and if DPPs can support this to some extent, it is positive from an environmental perspective and should be further researched. However, other measures, such as other policy instruments and behavioural changes, are also essential to tackle the environmental challenges of textile waste generation.
Keywords: digital product passport; textiles; reuse; recycling; sorting; second-hand